An analysis of Tuition Policy Discourses in Historically Black and White South African Tertiary Institutions - Maseko, Nokwazi Jacquiline (University of the Witwatersrand, Johannesburg, 2024)
This paper analyses the discourses around tuition policies in Historically Black and Historically White Institutions. This was motivated by the move towards incorporating discourse analysis into policy studies, contributing to the literature regarding discourse in higher education tuition policies, and understanding how discourse affects policy decisions. All these are aimed at addressing the shortfalls in tuition policy which contribute to issues such as the ongoing student protests. Semi structured interviews were conducted with 11 participants and were analysed using the Critical Discourse Analysis tools provided by Machin and Mayr (2012). The analysis showed that the historical discourses and personal ideologies held by those in power influence policy decisions. The study concluded that a reflexive and discourse orientated approach in the policies of HBIs and HWIs would promote policy solutions that are tailored for each institutional type, and this may ultimately decrease the frequency of tuition related protests
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management In Governance and Management to the Faculty of Commerce, Law, and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: Critical Discourse Analysis; Tuition Policy; Historically Black and Historically White Institutions; SDG-4: Quality education